(untitled) (Research, Society and Development, 2022)
Objective: to describe public health policies in attention to the LGBTQIA + population. Methods: this is an integrative literature review, using the Scielo, LILACS and BDENF databases. Results: in view of the theme, four (4) axes stand out as a result: Legal foundation milestones in health care for the LGBTQIA+ population; Responsibilities and attributions related to the Ministry of Health; Responsibility and assignments related to state health departments; Responsibilities; assignments related to municipal health departments. Conclusion: thus, the need for greater training of health professionals for the reception can be highlighted. and providing services plus services to this population. Becoming a more holistic, comprehensive and equitable service.